Oral health management in hypertensive patients addressing coated tongue caused by antihypertensive medication use: a case report - Tanumiharja, Marvin Jaya Setiadi; Tanumiharja, Leonardo Jaya Setiadi; Lelyana, Shelly; Kamil, Seno Muhammad (Universitas Padjadjaran, 2025)
Introduction: Hypertension is a chronic condition characterized by elevated blood pressure, often accompanied by symptoms such as headaches, epistaxis, and palpitations. Coated tongue is a clinical condition in which the tongue's surface develops a pseudomembrane due to accumulated debris, non-desquamated keratin cells, and microorganisms, such as bacteria and fungi. This study aims to explore the potential relationship between hypertension and coated tongue, emphasizing the importance of oral hygiene in hypertensive patients. By examining a clinical case, the research highlights the role of tongue cleaning in managing coated tongue and improving oral health. Additionally, it underscores the need for patient education and adherence to proper oral hygiene practices to achieve better treatment outcomes.Case Report: A 49-year-old female patient presented to Sartika Asih Bhayangkara Hospital with complaints of persistent bad breath for one month. She reported white spots on her tongue causing discomfort but no pain. The patient reported brushing her teeth one to two times daily but had never cleaned her tongue. She had a history of hypertension and was one amlodipine therapy.Conclusion: Coated tongue in hypertensive patients can be managed through regular tongue cleaning after brushing. Effective communication, education, and patient cooperation are crucial for optimal treatment outcomes.